Electronic health record system for rural communities at Borneo Island - Loh, Gary CheeWyai; Cheah, Wai Shiang (American Scientific Publishers, 2015)
Electronic health record system is crucial to promote health awareness in the rural remote places in Sarawak. It is able to record and monitor the personal health of each community member without being their physically. However, into what extends the EHR technology is relevant and applicable to rural communities in Borneo, Sarawak. This paper reviews the current EHR technologies in related to constraints environment within rural areas of Borneo, Sarawak. Work had been done to introduce an electronic health record system, Sympulse, to rural community, Sarawak two years ago. Although the project is pending due to some financial difficulties, we argue that the current EHR technologies are still inadequate to work in constraints environment. In this paper, requirements of a constraint based EHR system are reported. This is followed by details analysis and comparison of the proposed EHR system with others state of the art EHR technologies. From the findings, some research challenge and directions are elaborated. It can be served as a guideline to design and develop a constraint based EHR system.